The Impact of the Global Energy Crisis on Energy Law Policy and Regulatory Effectiveness in Indonesia - Wibowo, Teguh; Mangar, Irma; Rhozaq, Miftahul (Journal of Development Research, 2026)
The global energy crisis is a strategic phenomenon that has a wide impact on the formation and implementation of energy law policies in Indonesia. The imbalance between increasing energy demand and limited fossil energy sources, accompanied by geopolitical dynamics and fluctuations in energy prices, puts Indonesia in a vulnerable position. Although previous research has discussed the economic and policy impacts of the global crisis, there are still legal gaps regarding the effectiveness of national energy regulatory frameworks in responding to crises in an adaptive and sustainable manner. In addition, previous research has not comprehensively explained the relationship between the global energy crisis and regulatory disharmony, legal certainty, and institutional capacity in the implementation of energy policy in Indonesia. This study aims to analyze the influence of the global energy crisis on the direction of energy law policy and the effectiveness of its implementation. The method used is normative legal research with a statutory and conceptual approach through literature studies and descriptive qualitative analysis. The results of the study show that energy legal policies in Indonesia are still reactive, partial, and short-term oriented, causing legal uncertainty and weak integration of sustainable policies. This research offers doctrinal contributions in the form of adaptive energy law concepts based on energy security, regulatory harmonization, and the sustainability of national energy governance.